2020
DOI: 10.1111/eip.13002
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of clinical outcomes beyond psychosis in the ultra‐high risk for psychosis population

Abstract: Aim: Several prediction models have been introduced to identify young people at greatest risk of transitioning to psychosis. To date, none has examined the possibility of developing a clinical prediction model of outcomes other than transition. The aims of this study were to examine the association between baseline clinical predictors and outcomes including, but not limited to, transition to psychosis in young people at risk for psychosis, and to develop a prediction model for these outcomes.Methods: Several e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 76 publications
(92 reference statements)
0
11
0
1
Order By: Relevance
“…Although a multitude of factors have been identified that contribute to one’s susceptibility for conversion to psychosis, such as the presence of unusual content of thought, low functioning and functional decline [ 10 , 11 , 12 ], personality features [ 13 ] and personality disorders [ 14 , 15 ], how basic differences in multidimensional psychopathology can have a differential impact on course and outcomes is still unclear. Further studies are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Although a multitude of factors have been identified that contribute to one’s susceptibility for conversion to psychosis, such as the presence of unusual content of thought, low functioning and functional decline [ 10 , 11 , 12 ], personality features [ 13 ] and personality disorders [ 14 , 15 ], how basic differences in multidimensional psychopathology can have a differential impact on course and outcomes is still unclear. Further studies are needed.…”
Section: Introductionmentioning
confidence: 99%
“…It would seem that the presence of a PD does not affect clinical outcomes, irrespective of a transition to full-blown psychotic disorder. For example, a recent investigation by Polari et al(15) demonstrated that an additional diagnosis of borderline personality disorder was not associated with poorer outcomes, in terms of the recurrence, relapse, and remission of APS, as well as general functioning. However, further research is needed, and these results should also be replicated for outcomes other than APS.…”
mentioning
confidence: 99%
“…This supports the clear need for care in the UHR group and that treatment is appropriate and fully justified (Fusar‐Poli et al, 2013). Furthermore, a high level of baseline general psychopathology seems to be an important predictor of poor outcomes broadly defined in the UHR population and therefore an important element to respond to in this population (Polari et al, 2020). Regarding cognitive problems and biases, the scores of the present UHR sample were comparable to those with later‐stage schizophrenia spectrum disorders.…”
Section: Discussionmentioning
confidence: 99%